Pemberdayaan Masyarakat Melalui Digitalisasi Peningkatan Usaha Mikro Kecil dan Menengah (UMKM) di Desa Walay Kecamatan Abuki Kabupaten Konawe - Milyan Milyan; Sitti Rahmatyah; Tahmid Ansar; Iin Anggraeni; Hikmah Hidayat; Feriyanto Feriyanto (Jurnal Pelayanan Hubungan Masyarakat, 2023)
This community service activity was carried out in Walay Village, Abuki District, Konawe Regency. The purpose of this service activity is to foster a new enthusiasm for entrepreneurship for business actors through digitalization to increase MSMEs. The delivery of the service material that we carry out is divided into three stages, namely preparation, counseling/training and discussion. In the preparation stage we collect data from MSME partners to study the situation and conditions of the partners. The results of the evaluation, MSME business participants in Walay Village were grouped based on the use of digital marketing in doing business, namely: As many as 61.90% or 13 participants in MSME digitization activities, did not really understand the use of digital technology in doing business. and there were 38.10% or 8 participants in the MSME digitization activities who had used marketing methods by accepting orders via digital, in this case social media, where social media is Facebook and WhatsApp